2021
DOI: 10.3390/vaccines9030211
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic Predictors of Severe COVID-19

Abstract: According to an analysis of published data, only 20% of patients with the new coronavirus infection develop severe life-threatening complications. Currently, there are no known biomarkers, the determination of which before the onset of the disease would allow assessing the likelihood of its severe course. The purpose of this literature review was to analyze possible genetic factors characterizing the immune response to the new coronavirus infection that could be associated with the expression of angiotension-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 66 publications
0
38
0
4
Order By: Relevance
“…It was previously reported that patients with severe COVID-19 showed higher leukocyte and neutrophil counts, a higher neutrophil-to-lymphocyte ratio (NLR), and lower levels of monocytes, eosinophils, and basophils compared to those in patients with moderate disease severity [ 3 , 5 , 7 , 30 , 31 , 32 ]. In addition, a higher neutrophil count and NLR were associated with the severity of infection [ 30 ] and could be predictors of a poor prognosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that patients with severe COVID-19 showed higher leukocyte and neutrophil counts, a higher neutrophil-to-lymphocyte ratio (NLR), and lower levels of monocytes, eosinophils, and basophils compared to those in patients with moderate disease severity [ 3 , 5 , 7 , 30 , 31 , 32 ]. In addition, a higher neutrophil count and NLR were associated with the severity of infection [ 30 ] and could be predictors of a poor prognosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, lymphopenia with decreased absolute counts of CD4+ and CD8+ T cells, B cells, and natural killers (NK) cells have been detected in patients with COVID-19, excluding mild forms [ 3 , 4 , 5 , 6 , 7 ]. Decreased levels of total T cells as well as CD3+CD4+ and CD3+CD8+ subsets were primarily observed in elderly patients and were associated with infection severity and with the need for intensive care unit hospitalization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ERAP2 and its homolog ERAP1 constituted an efficient filter to epitope presentation by greatly limiting the diversity of virus antigenic peptides sequences produced, suggesting the promising value of ERAP2 in SARS-CoV-2 immunogenicity studies and vaccine design (41). The rs150892504 mutations in the ERAP2 gene were believed to be a genetic factor related to severe life-threatening complications in individuals infected with coronavirus (42). Since ERAP2 was involved in the renin-angiotensin system (RAS), ERAP2 dysfunction was hypothesized to exacerbate the symptomatology and prognosis of the SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…An important feature in the development of PCS after the asymptomatic/mild form is the predominance of female patients [14,20,68]. It is known that the female gender is a protective factor against the development of severe infections [69]. This is facilitated by several physiological characteristics, in particular:…”
Section: The Hypothesismentioning
confidence: 99%